Important insect, pests diseases in arid crops and their management - Singh, S. K.; Patel, Nisha; Kaul, R. K.; Jadon, K. S. (Indian Farming, 2018)
In arid and semi-arid regions majority of crops are attacked by blights, leaf spots, powdery mildews, downy mildews, soil-borne pathogens, viral diseases, white-flies, jassids, aphids, weevils,beetles and termites causing substantial damages and yield reduction. Nematode damage in arid< region is observed mostly in vegetables and fruit crops. Root-knot, reniform, root lesion and stunt nematode are the major nematode pests on these crops. Besides prophylactic management cultural practices, need-based curative integrated pest management practices of major diseases and insect pests are described.